(untitled) (Asian Journal of Medical and Biological Research, 2021)
The burden of serious pneumococcal disease is the heaviest in the developing world that focuses on its diagnostic importance. The incidence of pneumonoccoal disease in different regions of the world is not caused by some specific serotypes or serogroups of pneumonocci rather they are randomly distributed in population. A total number of 412 nasopharyngeal swab samples were cultures between January 2010 and December 2012. All the isolates were serotyped by using chessboard modification of quellung methods. A total of 102 S. pneumoniae isolates were found. The distribution among age groups shows that age groups 15 years and over 60 years are more frequent. The most common serotypes were 20 (17.6%), 33(16.7%), 6 (15.7%), 19 (14.7%) and 23 (10.8%) types. The addition of a pneumococcal vaccine (PCV) covering the prevalent serotypes in the immunization program could be useful for reducing the burden of pneumococcal diseases. Asian J. Med. Biol. Res. December 2020, 6(4): 618-622